Pengaruh Perencanaan Pajak, Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Nilai Perusahaan - Talizaro Bawamenewi; I Gede Adi Indrawan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explain and provide empirical evidence regarding the tax planning, firm size, and sales growth on firm value in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This study uses Effective Tax Rate (ETR) to measure tax planning, natural logarithm of total assets (LN) to measure company size, Growth (SG) to measure sales growth, and Price to Book Value (PBV) to measure company value. This study uses a quantitative approach, with data collection techniques in the form of documentation and library research. It is categorized as secondary research, which seeks to determine the relationship between variables. The population consists of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) with reporting periods from 2020 to 2024. The sampling technique used is purposive sampling, resulting in 165 sample data points from 33 companies that meet the research criteria. The analytical method applied is descriptive statistical analysis, including classical assumption tests, coefficient of determination tests, and partial t-tests. Data testing is conducted using multiple linear regression analysis, supported by Microsoft Excel and E-Views version 12 software. The results show that simultaneously, tax planning, sales growth, and firm size have an effect on firm value. However, partially, tax planning and sales growth do not affect firm value, while firm size has a significant effect on firm value.